Identifikasi sebaran kerentanan kekeringan pertanian menggunakan analytical hierarchy process (ahp) di kabupaten Temanggung - Ikaf Fajar Maulana; Sudaryatno Sudaryatno; Retnadi Heru Jatmiko (Jurnal Teknosains, 2021)
The decreased rainfall in Indonesia is mainly influenced by the east monsoon so air pressure from the southern hemisphere which is dry will flow through Indonesia. In a relatively long time, this may cause drought condition on agricultural land in Indonesia in general and in Temanggung Regency in particular. In addition, ENSO (El Nino Southern Oscillation) contributed to the decreased rainfall in Indonesia. This phenomenon will be more intensive and extreme with the existence of global warming. The identification of vulnerability of agricultural drought is an effort to mitigate disasters. This study aims to determine the distribution of agricultural drought and determine the factors that influence agricultural drought in Temangung Regency. The research method used the Analytical Hierarchy Process (AHP) to build a model of agricultural drought vulnerability by considering several factors. The results showed that the area of agricultural land which is vulnerable and very vulnerable  to drought is 86,2 km2 and 74,14 km2, while agricultural land with moderate vulnerability is 208,21 km2, and agricultural land which is not vulnerable and very not vulnerable to drought is 128,15 km2 and 267,33 km2. The main factor as a determinant of agricultural drought in Temanggung Regency is rainfall. Meanwhile, the next factor is the respective land cover and soil texture. This research concludes that the effect of slope is not a big impact on agricultural drought in Temanggung Regency.